Muslim women mystics the life and work of Râbia and other women mystics in Islam - Smith, Margaret 1884-1970 (Great Islamic thinkers., 2001)
This book is an authoritative account of the life and teachings of the ninth-century Muslim saint, Rabia, and represents the first complete biography of this unique individual. Discussing the place of Rabia in Islamic tradition, Dr Smith offers a survey of the female saints and mystics of the Muslim world, providing an unusual insight into women's impressive contribution to the rich heritage of Islam.